Beyond Primacy: A Stakeholder Theory of Corporate Governance - Stoelhorst, J. W.; Vishwanathan, Pushpika (Academy of Management Review, 2024)
We develop a stakeholder theory of corporate governance grounded in classical property rights theory, adopting the view that governance should help free individuals to maximize their collective welfare. In contrast to the agency view of corporate governance, we submit that the central problem in corporate governance is to devise coalitional contracting solutions to the collective action problems inherent in team production and team innovation. Agency problems and other contracting problems resulting from shirking, hold-up, market power, and externalities are best understood in this context. We develop design principles for the allocation of property rights to mitigate each of these contracting problems by reducing stakeholders’ vulnerabilities to opportunistic behaviors. We extend earlier efforts to build a stakeholder theory of corporate governance by considering a more comprehensive set of transaction problems and analyzing the comparative efficiency of different governance arrangements for different types of firm–stakeholder relationships and different economic contexts. One conclusion from our theory is that giving primacy to shareholders, or any other group of stakeholders, is a comparatively inefficient solution to governing the modern global and knowledge-driven corporation. We discuss the implications of our theorizing for the debate about the purpose of the firm.